Anodizing Al–Si Foundry Alloys: A Critical Review. Issue 4 (30th January 2022) - Scampone, Giulia; Timelli, Giulio
Abstract : Compared with pure aluminum and wrought aluminum alloys, Al foundry alloys are more difficult to be anodized. The high content of alloying elements prevents the uniform growth of the Al oxide layer and enhances the embedding of defects in the anodic film. The microstructure of the substrate and the anodizing parameters play a key role in the final quality of the oxide layer. Variations in the chemical composition, casting process, and pre‐ and post‐anodizing treatments can significantly affect the anodizing response. This work aims to critically review the main factors influencing the growth and morphology of the anodic layer in Al–Si foundry alloys. In particular, the effects on the oxide thickness, surface mechanical properties, and corrosion resistance are discussed in detail. Abstract : Compared with pure aluminum and wrought aluminum alloys, Al foundry alloys are more difficult to be anodized. This work aims to critically review the main factors influencing the growth and morphology of the anodic layer in Al–Si foundry alloys. In particular, the effects on the oxide thickness, surface mechanical properties, and corrosion resistance are discussed in detail.